2016
DOI: 10.1099/jgv.0.000584
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus PB1-F2 protein prolongs viral shedding in chickens lengthening the transmission window

Abstract: Avian influenza is a significant economic burden on the poultry industry in geographical regions where it is enzootic. It also poses a public health concern when avian influenza subtypes infect humans, often with high mortality. Understanding viral genetic factors which positively contribute to influenza A virus (IAV) fitness – infectivity, spread and pathogenesis – is of great importance both for human and livestock health. PB1-F2 is a small accessory protein encoded by IAV and in mammalian hosts has been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 39 publications
7
59
0
Order By: Relevance
“…This sample also contained the PB1-F2 S66 marker, which has been associated with increased pathogenicity in mammals (Conenello et al, 2011). All sequenced PB1 segments showed either the 87 or 90 amino acid-long PB1-F2 protein sequence, which is common in isolates from avian species (James et al, 2016). We also found N and T at position 66; interestingly, PB1-F2 T66 was only found in samples (n = 3 samples) sequenced through swab-NGS.…”
Section: Discussionmentioning
confidence: 74%
“…This sample also contained the PB1-F2 S66 marker, which has been associated with increased pathogenicity in mammals (Conenello et al, 2011). All sequenced PB1 segments showed either the 87 or 90 amino acid-long PB1-F2 protein sequence, which is common in isolates from avian species (James et al, 2016). We also found N and T at position 66; interestingly, PB1-F2 T66 was only found in samples (n = 3 samples) sequenced through swab-NGS.…”
Section: Discussionmentioning
confidence: 74%
“…Duck farming often involves raising and storing ducks in open bodies of water, which introduces the risk for wild waterfowl to mix with farmed ducks and transmit influenza viruses. In addition, studies have shown longer virus shedding times for LPAI‐infected ducks, up to 11.5 days, compared with LPAI‐infected chickens, up to 6 days (Hénaux & Samuel, ; James et al, ). Therefore, poultry traders with larger numbers of unsold ducks could increase the transmission window for ducks to infect chickens, especially as unsold ducks may have repeated exposures to wild waterfowl when traders store unsold ducks at home.…”
Section: Discussionmentioning
confidence: 99%
“…Contact transmission relies on the transfer of particles to mucous membranes directly, or via a fomite intermediate. tropism [15,[71][72][73][74][75][76]. One of the key molecular markers that facilitates adaptation of an AIV from wild aquatic birds to poultry is the deletion of amino acids from the stalk domain of NA, which have been shown to mediate the switch to respiratory tropism in chickens [77,78].…”
Section: H9n2 Virus Transmission and Host Tropism In Poultrymentioning
confidence: 99%
“…One of the key molecular markers that facilitates adaptation of an AIV from wild aquatic birds to poultry is the deletion of amino acids from the stalk domain of NA, which have been shown to mediate the switch to respiratory tropism in chickens [77,78]. There is good evidence to suggest that many LPAIV strains transmit by the airborne route, the oral-faecal route and the waterborne route [15,75,79]. However, the favoured mechanism of transmission between individuals varies by host species and viral strain.…”
Section: H9n2 Virus Transmission and Host Tropism In Poultrymentioning
confidence: 99%